Green lacewings (of Florida) Neuroptera: Chrysopidae - Lionel A. Stange (EDIS)
The Chrysopidae are one of the largest and economically most important families of the Neuroptera. There are about 1,300 currently recognized species included in about 87 genera and three subfamilies (Brooks and Bernard 1990) in the world. In Florida, there are 22 species in 9 genera, all placed in the subfamily Chrysopinae (Penny et al. 1997). The larvae are voracious predators of small, comparatively soft-bodied arthropods such as aphids, scale insects, whiteflies, thrips, insect eggs, and other prey (Muma 1959; Canard et al. 1984). For this reason, they are used widely in biological control. The adults are usually predators, but a few species only feed on pollen. This 4-page fact sheet includes Key to the Genera of Green Lacewings of Florida. Written by Lionel A. Stange, and published by the UF Department of Entomology and Nematology, October 2012.